Model of learning skills of ippon seoinage technique of judo sport - Samsul Bahri Sani; firmansyah Dlis; Widiastuti; Oman Uju Subandi (Mamaos: Journal Physical Education, Sport and Art, 2026)
The purpose of the research is to produce a Learning Model of Ippon Seoinage Slamming Skills for Judo Sports Branch. This research was carried out through a Research and Development (R&D) approach. The researcher conducted research by referring to the ADDIE development model which consists of five stages, namely analysis, design, development, implementation, and evaluation). The research sampling technique carried out in this study is 1 research subject of 30 students. Data analysis used an analysis of the effectiveness test of the Ippon Seoinage Technique Slamming Skills Learning Model for Judo Sports using SPSS. The results of the research are in the form of (1) Learning Model of Ippon Seoinage Technique Slamming Skills in Judo Sports (2) Learning Model of Ippon Seoinage Technique Slamming Skills in Judo Sports .which presents 16 Learning Models of Ippon Seoinage Technique Slamming Skills in Judo Sports. (3) Product Evaluation: That there is an improvement in the skill ability of the Ippon Seoinage Technique for Judo Sports Athletes which is developed based on the results of the effectiveness test using SPSS. Obtained mean = -shows the difference from pre-test and post-test, t-count result = -11.02, df =29 and p-value = 0.000 < 0.05 which means there is a significant difference between before and after the treatment of the Judo Sports Ippon Seoinage Slamming Technique Model (4) obtained mean = -showing the difference between pre-test and post-test, t-count result = -11.02, df =29 and p-value = 0.000 < 0.05 which means there is a significant difference between before and after given treatment of the Ippon Seoinage Slamming Technique Model of Judo Sports